Contemporary jewelry definitions (ModaPalavra e-periódico, 2017)
Contemporary jewelry terminology is open to many criticism and weaknesses as it is confronted with the classic definition of jewelry and also often attached to the historical widespread idea of adornment and jewelry to modernity. Therefore one of the this article issues is to approach about what it is contemporary jewelry and how it can be defined. Thus, we present the topics related to the jewel discussion in contemporary times that are organized into a set of assumptions and approaches that help us provide an overview about the contemporary jewelry.
Keywords: jewelry; jewel; contemporary